High performance perovskite LEDs via SPR and enhanced hole injection by incorporated MoS2. (3rd March 2021) - Sun, Dongwei; Zhang, Ke; Mei, Sijiong; Xu, Jinxia; Jiang, Yan; Xiao, Xiangheng; Zhou, Yuanming; Mei, Fei
Abstract: Organic–inorganic hybrid perovskites have attracted widespread attention in relation to light-emitting diodes (LEDs) due to their excellent properties. However, the imperfect energy band alignment between the perovskite and poly(3, 4 ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) limits the device's performance. Here, we have investigated the effect of blending MoS2 in PEDOT:PSS and the resulting performance of perovskite LEDs (PeLEDs). We found that the doping of MoS2 can optimize the energy barrier and promote hole injection, significantly improving the current efficiency (CE) of PeLEDs, which can be attributed to the distinguished electrical conductivity and improved charge injection balance. At the same time, the local surface plasmon resonance effect with Au nanoparticles (NPs) is also introduced to reduce the nonradiative recombination and effectively promote light emission to further improve the performance of PeLED devices. Compared to the control PeLEDs device with undoped PEDOT:PSS as the hole transport layer, a 223% enhancement in maximum CE and a 130% enhancement in maximum luminance are achieved, with an optimal volume ratio for the PEDOT:PSS:MoS2 of 1:0.4 and Au NPs of 10%. Thus, the optimization combination of MoS2 and Au NPs is an excellent approach to improve the performance of PeLEDs, thereby increasing the potential applications of PeLED devices.